Linda, as in the Linda murder : an Evert Bäckström novel - Persson, Leif G. W. (Vintage crime/Black Lizard., 2016)
The first in a trilogy of novels centered around the investigations of a Swedish police officer, Detective Superintendent Evert Bäckström, of the National Murder Squad.